Blended Learning: Can It Be a Solution to Improve Digital Literacy and HOTS for PGSD Students in a Pandemic Situation? - Dewi, Ririn Andriani Kumala; Fatkhiyani, Kiki (Universitas Pendidikan Ganesha, 2021)
The Covid-19 pandemic in the industrial revolution 4.0 era transformed traditional learning into bold-based learning through distance learning (PJJ). However, its implementation still encounters several obstacles, such as the lack of digital literacy skills. One of the solutions offered is blended learning, which combines traditional learning with learning to complement each learning method's shortcomings. The purpose of this study is to prove whether or not blended learning affects increasing digital literacy and HOTS of PGSD students. The methodology used is experimental research with Pre-Experimental Design with One-Group Pretest-Posttest Design model. The sample in this study was 55 PGSD students. The instruments used are digital literacy questionnaire sheets and HOTS test sheets. The technique used to analyze the data is descriptive qualitative, quantitative, and inferential statistics. Test Results Paired sample t-test produces sig values. (2-tailed) 0.000 is less than 0.05. It means that blended learning affects digital student literacy skills. The results of the n-gain test for increasing digital literacy after applying blended learning obtained n-gain of 0.56 in the medium category and the results of the student HOTS n-gain of 0.55 also in the medium category, so it can be said that there is an effect of blended learning on literacy improvement. Digital and student HOTS.